REPRODUCTIVE AND CHILD HEALTH ISSUES IN KERALA - MALA RAMANATHAN
Kerala has an impressive record in the area of reproductive and child health when compared to the rest of India. The fertility rate is said to be well below what is needed for replacement and its mortality rates are extremely low. It enjoys low infant mortality rates and also low adult mortality rates. Epidemiological transition is well under way and even if the infectious diseases have not been completely eradicated, chronic diseases do contribute significantly to the total morbidity within the state. The usual parameters of reproductive health like maternal mortality ratio, maternal morbidity, unmet need for family planning, abortion, HIV prevalence, low birth weight babies, and the nutritional status of mothers and children warrant a discussion in the present context